2018
DOI: 10.12659/msm.910808
|View full text |Cite
|
Sign up to set email alerts
|

miR-339-5p Increases Radiosensitivity of Lung Cancer Cells by Targeting Phosphatases of Regenerating Liver-1 (PRL-1)

Abstract: BackgroundRadiotherapy is the most effective non-surgical modality in lung cancer treatment, and microRNAs (miRNAs) have been suggested as key regulators in radiosensitization. Herein, we explored the specific function of miR-339-5p in the radiosensitivity of lung cancer cells.Material/MethodsRadiosensitivity was assessed by cell viability (CCK-8 assay), cell apoptosis, and cell cycle changes (flow cytometry). qRT-PCR and subsequent Western blot assays were used to determine the expression of miR-339-5p and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Similar to lncRNA, miRNA is involved in multiple cancers and functions as the regulator of radiosensitivity. 52 , 53 For instance, miR-99a enhances the radiosensitivity of NSCLC cells by targeting the expression of mammalian target of rapamycin. 54 Upregulated miR-328-3p makes NSCLC cells more sensitive to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to lncRNA, miRNA is involved in multiple cancers and functions as the regulator of radiosensitivity. 52 , 53 For instance, miR-99a enhances the radiosensitivity of NSCLC cells by targeting the expression of mammalian target of rapamycin. 54 Upregulated miR-328-3p makes NSCLC cells more sensitive to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Haijun Li et al reported that reduced miR‐339 expression predicts the poor prognosis of GC. In ovarian cancer, miR‐339 inhibited the tumor progress by directly regulating NACC1 and Bcl6 while miR‐339 regulated the metastasis of colorectal cancer via targeting PRL‐1 . LncRNA RP11‐81H3.2 might function as a ceRNA and sponge the miR‐339.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of miRNAs is essential for multiple biological processes, such as cell proliferation and differentiation (12,13). However, the aberrant expression of certain miRNAs and the subsequent dysregulation of target gene expression have been associated with the genesis and progression of multiple types of cancer (14,15). Downregulation of miRNA (miR)-124-5p is associated with lymphangiogenesis in human gastric cancer (16); additionally, low expression levels of miR-124-5p have been detected in glioma and colorectal cancer cells (17,18).…”
Section: Introductionmentioning
confidence: 99%